Genetic Transformation of Transcription Factor (35S-oshox4) Gene into Rice Genome and Transformant Analysis of hpt Gene by PCR and Hygromycin Resistance Test - ENUNG SRI MULYANINGSIH; REGY HERMAWAN; INEZ HORTENZE SLAMET LOEDIN (Society for Indonesian Biodiversity, 2009)
Global warming, climate change and crop extensification in marginal dryland areas are related to long dry season and waterdeficit. The water availability is an important factor in improving plant production. Application of drought tolerant rice cultivars is one of several options that might be used. Genetic engineering at the level of transcription factors is particularly promising strategy to develop drought tolerant rice varieties. Transcription factors regulate a wide range of target genes in which of them contribute to stress tolerance. HD Zip genes are transcription factor that potential in the adaptation of plants to some environment stresses including water deficit. HD-ZIP oshox4 (oryza sativa homeobox) gene controlled by 35S promotor is inserted into pCAMBIA 1300 vector with hpt (hygromycin) gene as a selectable marker. The aim of this research is to obtain transgenic rice plant from transformation with 35S-oshox4 plasmid, segregation analysis of marker gene (hpt) by PCR method at T0 and T1 generation, and hygromycin resistance analysis of seeds. Recombinant plasmid was transformed into rice genome of IRAT 112 and rojolele cultivars using Agrobacterium tumefaciens. The results showed thattransformation efficiency of IRAT 112 was 5.7-13.6% and 26-66,7% for rojolele. While regeneration efficiency for IRAT 112 is 4.7-43.7% and 23-44.1% for rojolele. The result of hygromycin resistance test at T1 seeds were obtained 14 lines cv. rojolele segregation Mendelian for hpt gene. The PCR analysis using specific primers for hpt gene at the parent (T0) from 14 lines showed that 7 lines contain the gene. At the second generation (T1), PCR analysis using hpt primers showed that 3 from 4 lines were followed Mendelian segregation pattern by the presence of specific band.Key words: HD-Zip oshox (oryza sativa homeobox), 35S-oshox4, hpt, Agrobacterium tumefaciens, PCR.